ANALISIS YURIDIS UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH TERKAIT PENGGUNAAN HAK INTERPLASI DAN HAK ANGKET DALAM MENILAI KEBIJAKAN KEPALA DAERAH - NAZADOLA. SH, A.2021141077, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis focuses on the analysis of juridical Law No. 23 of 2014 On Local Government related to the use of the right of interpellation and inquiry rights in assessing policy research daerah.Dari head writer using normative juridical research method, the conclusion: that. 1). that the minutes of the results of the trial related to the 1945 amendment of Article 20 A (2) does not occur debates and the theoretical foundation of the inclusion filosfis interpellation Rights and Rights of the questionnaire the rights inherent in the institution of Parliament. Debates that occur constitute only about whether or not the right of interpellation and inquiry rights included in the constitution as well as the order does not discuss the use of these rights. This is exactly the same as what is contained in Law No. 17 Year 2014 About the MPR, DPR, DPD and DPRD and Law Npomor 23, 2014 About the Regional Government. There is no official explanation, on the order of use of these rights. When examined in Law No. 12 of 2011 Concerning the Establishment of Laws Invitations, associated with the formulation of the norms contained in Article 106 paragraph (1) and article 159 paragraph (2) of the Law Npomor 23 2014 merely tabulations are associated with alternative or cumulative norm, but it does not explain the order in which the rights of parliament. Therefore, the authors argue that Article 106 paragraph (1) and article 159 paragraph (2) of the Law Npomor 23, 2014 should be read and implemented sequentially with the argument: a). is unethical and irrational to the right of inquiry used prior to the interpellation. Parliament must first request information from the head of the region in respect of their strategic policy and broad impact for the community and local residents. if the information requested to the head area is not satisfactory and is not considered sufficient and no assumption divergence or violations of the measures taken and designated head of the region, then the right of inquiry was conducted to investigate. b). if the Rights of the questionnaire prior to use, then the legal norms contained in Article 106 paragraph (1) and Article 159 paragraph (1) of Law No. 23 of 2014 which consists of three (3) letters namely a, b and c, will lose their meaning and conflicting. This is due, to use the Right to Expression of the conditions is a follow up of the interpellation and the right of inquiry. That is, Rights Expression can not be used, if Parliament only use the right of inquiry without first using the interpellation. Words or phrases